Effect of Continuous Care Combined with Constraint-Induced Movement Therapy Based on a Continuing Care Health Platform on MBI and FMA Scores of Acute Stroke Patients. (25th January 2022) - Yingying, Pan; Zang, Lixin; Wang, Xiaojie; Yang, Xiuqin
Abstract : Background and Objective . The study was carried out under the background that out-of-hospital rehabilitation of acute stroke patients is of great importance for the recovery of nerve and limb functions. We aimed to investigate the effects of continuous nursing combined with CIMT by a health platform on the limb motor function and quality of life in acute stroke patients. Methods . 68 acute stroke patients admitted to our hospital from July 2018 to July 2019 were selected as the study participants and divided into group A and group B based on the odd and even numbers of their admission numbers, with 34 cases in each group. Patients in group B accepted the routine rehabilitation exercise, while patients in group A accepted the continuous care combined with constraint-induced movement therapy (CIMT) under a health platform, so as to compare their upper limb function recovery by the Fugl–Meyer assessment (FMA) and improved median Barthel index (MBI). Results . The general information of the two groups were not obviously different (P  > 0.05) but comparable; after intervention, the FMA scores (38.42 ± 7.62 vs 31.22 ± 7.25) and MBI scores (78.63 ± 6.52 vs 70.24 ± 6.48) of patients in group A were significantly higher than those of group B (P  < 0.001); the activities of daily living (ADL) and trunk control test (TCT) scores at T1, T2, and T3 of group A were significantly higher than those of group B (P  < 0.05); at 6 months after discharge, the self-concept, self-care skills, self-care, self-responsibility, health knowledge level, and total ability scores of patients in group A were significantly higher than those in group B (P  < 0.05); the Generic Quality of Life Inventory-74 (GQOL-74) scores after intervention of the two groups were significantly higher than those before intervention (P  < 0.05) and those of group A were significantly higher than those of group B (72.13 ± 4.69 vs 63.19 ± 4.72; P  < 0.05); when comparing with group B, group A presented significantly higher walking speed and gait period and lower support phase (P  < 0.05). Conclusion . The combination of continuous care and CIMT under a health platform can effectively promote the rehabilitation of upper limb functions and improve the activities of daily living and trunk control for acute stroke patients, with an effect better than conventional rehabilitation exercises, which is worthy of promotion.